Rituximab Treatment in Acute Disseminated Encephalomyelitis Associated with Salmonella Infection - Ebru Kacmaz; Gurkan Bozan; Kursat Bora Carman; Omer Kilic; Mehmet Ozgur Arslanoglu; Ugur Toprak; Aslı Kavaz Tufan; Coskun Yarar; Ener Cagri Dinleyici (Case Reports in Pediatrics)
Acute disseminated encephalomyelitis (ADEM) is an inflammatory, demyelinating, and rapidly progressive disorder of the central nervous system. This condition is also known as postinfectious encephalomyelitis, and it is characterized by multifocal lesions in the brain and spinal cord with widespread neurological findings. High doses of intravenous (IV) methylprednisolone, intravenous immunoglobulin (IVIG), and plasma exchange (PLEX) treatments comprise the first-line therapy. There are limited pediatric case reports refractory to standard treatment. Here, we present the case of a 17-year-old girl diagnosed with ADEM associated with Salmonella infection, which was treated with rituximab.